Reiteration Used by the Participants of Warmadewa University Reading News Contest - Kadek Claria, Dewa Ayu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
Abstract -- This paper discusses about reiteration used by the participants of reading news contest conducted in Warmadewa University. Reiteration is part of lexical cohesion. The lexical cohesion has two functions; first to link between word and word, phrase and phrase within a text and second to indicate co-occurrence of words in which their meaning related in the same environment. The reiteration refers to first function of lexical cohesion. The theories applied to support this paper are the theory of cohesion from a book entitled Introducing Discourse Analysis by Nunan (1993) and a book entitled Cohesion in English by Halliday and Hasan (1976). The data of this paper taken from six texts made by the participants of the contest. The text contains with the participants’ perspectives on Indonesian culture in the globalization era. The data was analyzed by using qualitative method. Based on the result of the analysis, it is found that reiteration used in the text by the participants of reading news contest consists of repetition, synonym/nears synonym, superordinate and general word.   Keywords : Text; Lexical Cohesion; Reiteration